A study on the role of fluorine in titanium dioxide synthesis - Yeo, Chun Yi. (2011)
Fluorine doped titanium dioxide (TiO2) was prepared via hydrothermal synthesis using titanium tetrafluoride (TiF4) as the fluorine precursor. The properties of fluorine doped TiO2 were investigated by characterizing the samples of different fluorine precursor concentration using X-ray diffractometer (XRD), field emission scanning electron microscope (FESEM) and X-ray photoelectron spectroscopy (XPS). Introducing fluorine helps change the texture of TiO2 anatase phase. Increase in fluorine precursor concentration increases the percentage of energetic {001} facets in TiO2. Denser and more complete nanosheets are also obtained with higher fluorine precursor concentration. Fluorine precursor concentration of more than 0.12M shows saturation of energetic {001} facets. XPS results show that in order to have for fluorine atoms to dope into the lattice of TiO2, the fluorine precursor concentration has to be either more or less than 0.12M. This may be due to excessive fluorine atoms remain crowding on the surface of TiO2, causing the fluorine atoms (F ions) in the lattice of TiO2 to be undetectable by XPS. Another reason may be the amount of dangling bonds on the {001} facets which could be an important factor of whether the fluorine atoms could be doped into the lattice of TiO2.